The Russian ritual year and folklore through tourist advertising - Sedakova, Irina (Traditiones (Ljubljana), 2012)
This article analyzes the ritual year in modern Russia as reflected in tourism spam letters circulated between 2005 and 2012. These texts are the mainsource of data for this study because they illustrate major tendencies in governmental, commercial, and individual attitudes towards Russian traditional customs and official holidays. They also demonstrate how local heritage is being maintained and reconstructed, and how new myths and customs are appearing and developing to suit the needs of domestic tourism, a special ethnographic calendrical type.
Keywords: ethnology; Etnologija; customs; Šege; Pust; carnival; tourism; Turizem; Rusija; ljudske šege; pustovanje